COMPARISON OF GOVERNMENT SYSTEMS BETWEEN MALAYSIAN AND INDONESIAN - Dian Herlambang Dian; Muhadi Muhadi; Iskandar Muda; Raesitha Zildjianda (Law Faculty of Universitas Bandar Lampung, 2023)
In general, the Malaysian legal system is influenced by the British Common Law System legal tradition, while the Indonesian legal system adopts more of the Dutch civil law system tradition. In addition, the Islamic legal system and the customary law system also influence the national laws of each country. The comparative study of the constitutional law systems of Malaysia and Indonesia is a study of constitutional law using normative law research methods with a comparative law approach to examineWhat are the differences in the form of the state between Indonesia and Malaysia and how are the differences in the system of government between Indonesia and Malaysia. Based on the results of research through liberary research it was found that the institutional formats of Malaysia and Indonesia have differences both in terms of the form of the state and the system of government. Malaysia is a country that adheres to a federal type of state which includes a federal state and a state with a democratic monarchy system of government. While the State of Indonesia, in the form of a unitary state which includes central government and autonomous regions with a republican system of government with the principles of constitutional democracy.